PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM PADA PAUD REZEKI DESA KARTIASA KECAMATAN SAMBAS - Sri Nilawati; Hifza Hifza; Ubabuddin Ubabuddin (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
This study discusses the instilling of Islamic Religious Education Values ​​in PAUD Rezeki Kartiasa Village, Sambas District. This thesis is motivated by the Internalization of Instilling Islamic Educational Values ​​in Early Childhood At PAUD Rezeki Kartiasa Village as the 2nd (second) education place after education in the family environment. This research approach uses a qualitative approach with a Field Research pattern of research (field research). This study intends to examine the values ​​of worship, creed, and morals and to reveal methods and evaluations in inculcating Islamic religious education in Early Childhood Education institutions. The results showed that the methods of inculcating Islamic religious education values ​​in PAUD Rezeki Kartiasa Village were: a) Storytelling method, to instill moral values ​​and exemplary; b) The singing method, to instill the values ​​of spirit, life and awareness, because through the singing method children feel happy and happy; c) The method of playing, to instill moral values ​​related to the attitude of being willing to give in, cooperation, helping, queuing culture and respect for friends; d) The exemplary method, to instill moral values ​​so that they can behave and speak well and appropriately; and e) Question and answer method, to instill the value of courage and initiative.